Characterisation of steel composites fabricated by selective laser melting - Koh, Hwee Kang (Nanyang Technological University, 2021)
The advancement of using additive manufacturing (AM) technology to develop metal matrix nanocomposites (MMNCs) is gaining enormous attention due to their potential improvement in terms of physical and mechanical performances. This project covers the research using particle reinforced MMNCs with the aid of Selective Laser Melting (SLM) to present an analysis that will quantitatively address the potential change in mechanical properties including microhardness, microstructure, tensile properties. The nanoparticle, Fumed Silica, that is usually used in polymer matrix nanocomposites, was selected to be used in this experiment due to the cost effectiveness and thixotropy properties that could potentially bring unanticipated benefits in production of MMNCs using SLM technology. Over the course of this project, tests were carried out and the result have shown that hydrophobic and hydrophilic fumed silica successfully achieved a homogenous blend. The microstructure images from the test showed that denser dendrites had been produced. Marginal improvements were seen in the mechanical properties and grain refinement.